MAUIZAH METHOD IN LEARNING THE QURAN AS A CONCEPT OF MORAL AND SPIRITUAL EDUCATION BASED ON QS LUQMAN VERSES 12–19 - Aulia Tegar Wicaksono; Surahman's Grandson; Elan Sumarna (Al-Mubin, 2026)
This study aims to examine mauizah as a Quranic model of moral and spiritual education based on Surah Luqman verses 12–19 Employing a maudui thematic exegetical approach this qualitative library research integrates classical Quranic commentaries such as al Qurtubi alongside the contemporary interpretation of Tafsir al Misbah by Quraish Shihab in dialogue with Islamic educational and ethical thought In this study mauizah is conceptualized not merely as verbal advice but as a comprehensive pedagogical method characterized by gentle communication emotional proximity and the internalization of moral and spiritual values within the learners inner consciousness The findings reveal that Luqmans counsel constitutes a structured and progressive moral spiritual educational framework encompassing the cultivation of tauhid and syukr gratitude filial piety awareness of muraqabah and the development of istiqamah through salat amr maruf nahy munkar and sabr Furthermore the verse emphasizes social ethics through the cultivation of tawadu self restraint and refined communication These values are transmitted through an affective pedagogical approach that nurtures internal moral awareness rather than externally imposed obedience This study argues that mauizah represents a holistic humanistic and transformative model of Islamic education as it integrates cognitive understanding affective engagement and spiritual awareness in a balanced manner Consequently Quranic education grounded in mauizah offers a relevant and meaningful response to contemporary moral spiritual and character challenges in Islamic education